2020
DOI: 10.3390/ijerph17061972
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indoor Air Quality and Users Perception of a Renovated Office Building in Manchester

Abstract: Building renovations can adversely affect building occupants through the release of biological contaminants, gases and particulates. In this study, the research aim was to monitor the air quality of a renovated building and assess the impact of sick building syndrome (SBS) on the occupants. Post occupancy monitoring of the building was carried out after two months occupancy for the following environmental parameters: airborne microflora using an air sampler (SAS super 180) and a hand-held monitoring device (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Possible reasons for the observed time trends of reported symptoms in the present study could be multifactorial, involving, for example, workload of the office workers that may not have been consistent over time, as well as changes in office landscapes, construction, and building materials—affecting indoor climate and concentration patterns of air pollutants. Occupants of offices with higher concentrations of selected air pollutants have been shown to be more likely to report health symptoms in several recent studies [ 24 , 28 , 29 , 30 ], though no findings of such relationships have been reported [ 31 ]. Furthermore, trends in office layouts have changed during the last few decades, from cellular, private spaces, to more shared spaces and open-plan office landscapes [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for the observed time trends of reported symptoms in the present study could be multifactorial, involving, for example, workload of the office workers that may not have been consistent over time, as well as changes in office landscapes, construction, and building materials—affecting indoor climate and concentration patterns of air pollutants. Occupants of offices with higher concentrations of selected air pollutants have been shown to be more likely to report health symptoms in several recent studies [ 24 , 28 , 29 , 30 ], though no findings of such relationships have been reported [ 31 ]. Furthermore, trends in office layouts have changed during the last few decades, from cellular, private spaces, to more shared spaces and open-plan office landscapes [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In paper [45], the focus is on air exchange in the summer when considering energy savings. Posts [46][47][48][49] are devoted to the issue of air exchange in various types of buildings, the increase in CO 2 and its impact on users.…”
Section: Measurement Of Carbon Dioxide Concentration Valuesmentioning
confidence: 99%
“…It was concluded the low RH was also attributed to the season in which the sampling was performed (October–November), which is usually cool and dry for Jos and its environs [ 43 ]. Though the relationship between health, indoor air humidity and pollution is complex and challenging, several studies in the office environment have shown associations between low RH (5–30%), with increasingly prevalent complaints about perceived dry and stuffy air, and sensory irritation of the eyes and upper airways [ 44 , 45 , 46 ]. In a study of 484 office workers and 21 greenhouse employees in normal and well-ventilated office buildings, though dependent on psychosocial and environmental factors, low RH produced a few percentage reductions in visual acquisition for certain office tasks among young students that were exposed for 4 h, an effect that was expected to be more pronounced among the elderly.…”
Section: Resultsmentioning
confidence: 99%